SHARIA MICROFINANCE MODELS: A GRAMEEN BANK APPROACH FOR SUSTAINABLE CONSTRUCTION AND WELFARE ENHANCEMENT - Terminanto, Ade Ananto; Hamid, Abdul; Amalia, Euis (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2024)
This research aims to build a model for strengthening Sharia microfinance through an adapted Grameen Bank replica based on the pillars of leadership, collaboration, spirituality, and women's freedom. This research used a quantitative method to analyze a Grameen Bank replica or build a model for strengthening Sharia microfinance. It provides an early description of the model's independent and dependent variables using Path Investigation and Structural Equation Modeling (SEM). Data were gathered through participatory observation methods, interview techniques, and the distribution of SEM questionnaires to MFI managers and beneficiary customers. The findings indicate a link between the influence of the Grameen Bank-based Islamic Microfinance Institution system on partners in terms of leadership, cooperation, economy, community, and spirituality, as well as alternative strategies for strengthening Grameen Bank-based MFIs in improving the welfare of women's microbusiness groups. This research encourages more attention and implementation of Islamic microfinance models in an effort to improve social and economic welfare, especially among vulnerable groups such as women micro-entrepreneurs.